Thermal integration of a SOFC power generator and a Na–NiCl2 battery for CHP domestic application. (1st January 2017) - Antonucci, V.; Branchini, L.; Brunaccini, G.; De Pascale, A.; Ferraro, M.; Melino, F.; Orlandini, V.; Sergi, F.
Highlights: Integration of a SOFC generator and a Sodium Nickel Chloride battery is presented. Thermal integrations is considered as innovative solution. Domestic application is investigated also with economic analysis. Comparison with other micro-CHP systems is shown. The proposed system provides primary energy and economic savings. Abstract: In this study the integration of a Solid Oxide Fuel Cell (SOFC) prime mover and a high temperature electrochemical Sodium Nickel Chloride (SNC) battery as storage has been investigated. The aim is to fulfil a domestic user energy demand and to reduce the primary energy consumption in comparison with a reference conventional scenario, thereby, to enhance the total efficiency in a μ-CHP (Combined Heat and Power) application on a yearly basis. A realistic operational sequence of the SOFC-battery integration has been calculated using simple logic conditions. Both thermal and electric integration have been considered, where the innovative thermal integration has been proposed in order to exploit the SOFC residual heat for the battery stand-by feeding. The key advantage of this system architecture is that the SOFC is operated without major load variations close to constant load, resulting in longer lifetime and thus reducing total costs of operation. The thermal integration provides additional advantages, as calculated in this study. Eventually, a comparison with alternative μ-CHP technologies has been carried out, highlighting the potential of the system based on the SOFC. Benefits are mainly shown in terms of primary energy savings and admissible costs.